Razonabilidad de la cuenta propiedad planta y equipo, del Gobierno Autónomo Descentralizado de la parroquia "La Unión" período 2021. - Dulcey Ramos, Janina Anthonela (2022)
Theo decentralized autonomous parish government of La Unión is an entity that belongs to the public sector and is located in the parish of La Unión, which belongs to the Babahoyo canton, and must ensure the well-being of all the citizens that make up the parish and its different communities and sectors. neighboring to it. For its operation, it is necessary to have certain movable and immovable property that allows the work for which the creation of this institution was intended to be carried out, which is the administration of the resources assigned by the central government for the benefit of the parish and its inhabitants, part of resources, these include assets that can be personal property (computers, desks) or real estate (land, buildings) but which in turn must be correctly registered, classified and valued according to the regulations stipulated by law, with the objective of provide a correct functioning in the administrative and operational activities that the parish GAD has to execute; in addition to the goods that serve for the benefit of the community. The parish GAD must present its financial statements with all the accounts and subaccounts that they manage in an accounting cycle and within the financial statements is the property, plant and equipment account, which must present the values of the assets that it owns less the due depreciations and increases that they suffered in the event that an additional good has been acquired during the exercise of the fiscal period this information must be presented under the international accounting standards and norms and the norms stipulated by the central government, all this with for the purpose of fairly presenting such account.